2016
DOI: 10.18203/2320-6012.ijrms20163805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga on salivary cortisol in medical student

Abstract: INTRODUCTIONOver the decade, hundreds of studies have specifically focused on the effects of stressors on cortisol activation. The process by which this regulation is achieved is complex and our understanding of it has evolved markedly over the last century. Physical stressors, psychological stressors are capable of activating the HPA axis; a number of studies have reported that laboratory tasks can increase cortisol levels.1 Salivary cortisol offers a non-invasive and stress-free alternative to serum. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…It has been noted that the body physically responds to laughter, such as through an increase in the level of beta-endorphins, a decrease in stress hormones such as adrenaline, noradrenaline, and cortisol, an improvement in mental processes, and a decrease in blood pressure and muscle tension [ 32 , 42 ]. In the literature, studies have reported that laughter yoga also provides a significant decrease in salivary cortisol, which is considered a biological marker of stress [ [43] , [44] , [45] , [46] ]. In meta-analysis studies, it was found that laughter therapy is an effective complementary method and reduces anxiety levels [ 28 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the body physically responds to laughter, such as through an increase in the level of beta-endorphins, a decrease in stress hormones such as adrenaline, noradrenaline, and cortisol, an improvement in mental processes, and a decrease in blood pressure and muscle tension [ 32 , 42 ]. In the literature, studies have reported that laughter yoga also provides a significant decrease in salivary cortisol, which is considered a biological marker of stress [ [43] , [44] , [45] , [46] ]. In meta-analysis studies, it was found that laughter therapy is an effective complementary method and reduces anxiety levels [ 28 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Chang et al (2013) on seventh‐grade adolescents in Thailand, they found that laughter yoga provides a significant decrease in cortisol levels. Berk et al (2008) stated that laughter yoga provides a decrease in cortisol levels in healthy adult men, whereas Pandey et al (2016) found that laughter yoga significantly decreased salivary cortisol in medical students. Furthermore, Nagendra et al (2007) found that laughter yoga significantly reduced cortisol levels in office staff, whereas Fujısawa et al (2018) found that laughter yoga significantly reduced salivary cortisol in university students.…”
Section: Discussionmentioning
confidence: 99%
“…Students may be absent from school as a result of the stress they experience and that they can leave their nursing education without completing their education (Gebhart et al, 2020). Salivary cortisol is a possible biological marker of psychological stress (Pandey et al, 2016). For this reason, experimental studies that evaluate the successful stress coping techniques of nursing first grade students with an objective parameter such as salivary cortisol should be conducted in order to prepare for this challenging profession during the nursing education process (Arabacı et al, 2015; Gebhart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sağlık profesyonellerinin sağlığı geliştirmede kullanabilecekleri bir uygulama olan kahkaha yogası birçok alanda kullanıldığı gibi kadın sağlığı alanında da kullanılmıştır. 21,[34][35][36][37] Yapılan çalışmalarda kahkaha yogası pospartum dönemdeki kadınların doğum sonu yorgunluklarını azaltmada ve immün cevapları üzerine olumlu etkiler oluşturmuştur. 38,39 Menopoz dönemindeki kadınlara uygulanan kahkaha yogası da kadınların iyimserliğini ve benlik saygısını artırmış, depresyon düzeylerini azaltmıştır.…”
Section: Kahkaha Yogasının Kadın Sağlığı üZerine Etkileriunclassified